Association of nighttime physical activity with all-cause and cardiovascular mortality: Results from the NHANES - Yi, Jiayi; Wang, Lili; Guo, Jiajun; Sun, Ping; Shuai, Ping; Ma, Xiaoxiang; Zuo, Xiaojiao; Liu, Yuping; Wan, Zhengwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Nighttime physical activity (PA) has significant effects on human health. Whether excessive nighttime PA is associated with adverse long-term prognosis remains unknown. Methods: 3690 adults from the US National Health and Nutrition Examination Survey (NHANES) 2003–2006 with accelerometer monitor recording PA data were included. Nighttime PA was quantified by the nighttime to all-day PA intensity ratio (NAPAIR). Participants with the NAPAIR above the population median (0.17) were defined as the nighttime active population (NAP), otherwise as the daytime active population. All-cause and cardiovascular disease mortality status was acquired from the US National Death Index from their interview and physical examination date through December 31, 2015. Results: Among 3690 adults (weighted mean age 48.1 years), 1781 (weighted proportion 48.8%) were females. 1806 (48.9%) were determined as the NAP. During the follow-up period of up to 13.1 years (median, 10.7 years), 639 deaths occurred (heart diseases, 114). Multivariable Cox proportional hazards model showed that the NAP was associated with higher risks of all-cause (hazard ratio [HR], 1.46; 95% confidence interval [CI], 1.22–1.75) and cardiovascular disease (HR, 1.58; 95% CI, 1.03–2.41) mortality compared with the daytime active population, and each 0.1 increase in the NAPAIR was associated with 15% increased all-cause mortality risks. Conclusion: In this nationally representative prospective cohort study of a sample of United States adults, excessive nighttime PA was associated with a higher risk of death from all causes and cardiovascular disease.